If I were an ant - Moses, Amy.; Dunnington, Tom (New York : Childrens Press, 1992)
A child imagines how much larger things such as crumbs, puddles, trees, and even babies would seem to an ant.
"Level C, fluent"--Cover p. [4].
2.
2.3
K-3
P-2.
Keywords: Ants -- Fiction; Size -- Fiction; Ants -- Fiction; Size -- Fiction; Readers (Elementary).